Smallholder cocoa agroforestry systems; is increased yield worth the labour and capital inputs?. (February 2022) - Scudder, Micah; Wampe, Nathan; Waviki, Zephaniah; Applegate, Grahame; Herbohn, John
Abstract: CONTEXT: Smallholder cocoa agroforestry systems provide most of the cocoa produced world-wide and can improve the livelihoods of rural families in the tropics. However, many smallholder cocoa producers experience low cocoa yields due to generally poor management practices, pests, disease, and low soil fertility. In Papua New Guinea, pest and disease management systems have been developed to provide improved yields and revenues, but there has been limited uptake. OBJECTIVE: We hypothesized that the low uptake of these systems may be due to the improved yields not being sufficient to justify the required increase in labour and capital inputs. Our objective was to assess if the integrated pest and disease management systems were financially viable. METHODS: Our methods involved developing discounted cash flow models that incorporated Monte Carlo risk analysis software. We populated the models with labour inputs, costs, and revenue data collected in country, and from scientific literature. In addition to net present value, we evaluated the production systems with additional criteria we deemed appropriate for assessing the required labour inputs and capital outlays; return on labour; mean labour hours/day; mean annual capital outlays, mean hourly income, and mean annual income. RESULTS AND CONCLUSIONS: Our results show that under the current cocoa prices being received, all the production systems had a negative net present value, and a mean hourly income that was below the Papua New Guinea minimum wage and less than 1 USD/h. Furthermore, the progressive addition of labour inputs and capital outlays of the pest and disease management systems resulted in mean hourly incomes that are less than currently being received. These decreased hourly earnings may explain the low adoption of these technologies. SIGNIFICANCE: Financial analyses of new smallholder agroforestry technologies should be used to evaluate the viability and likelihood of smallholder technology adoption. Previous research on cocoa pest and disease management systems failed to account for costs related to labour and capital inputs. Even if farm family labour does not incur a direct cash outflow, it does represent an opportunity cost to farmers. Including additional criteria that measure financial returns to farmers relative to labour and capital requirements should be a part these assessments. These additional criteria can aid in evaluating all the economic thresholds that may impact if and how smallholders will incorporate new agroforestry technologies, which can help improve the success for agriculture-based development projects throughout the global tropics. Graphical abstract: Unlabelled Image Highlights: In Papua New Guinea, many smallholder cocoa farmers experience low cocoa yields despite receiving training in pest and disease management systems. We hypothesized that the low system uptake may be due to the improved yields not being sufficient to justify the increase in labour and capital. We developed discounted cash flow models that incorporated Monte Carlo risk analysis software to evaluate the systems against selected criteria. The pest and disease cocoa management systems provided lower mean hourly earnings than the low input cocoa system and this limited adoption. Smallholder agroforestry technologies should be evaluated for viability and likelihood of smallholder technology adoption during development.